Myocardial reperfusion reverses the J-curve association of cardiovascular risk and diastolic blood pressure in patients with left ventricular dysfunction and heart failure after myocardial infarction: insights from the EPHESUS trial. (2nd March 2020) - Böhm, Michael; Ferreira, João Pedro; Mahfoud, Felix; Duarte, Kevin; Pitt, Bertram; Zannad, Faiez; Rossignol, Patrick
Abstract: Aims: The described association of low diastolic blood pressure (DBP) with increased cardiovascular outcomes could be due to reduced coronary perfusion or is simply due to reverse causation. If DBP is physiologically relevant, coronary reperfusion after myocardial infarction (MI) might influence DBP–risk association. Methods and results: The relation of achieved DBP with cardiovascular death or cardiovascular hospitalization, cardiovascular death, and all-cause death was explored in 5929 patients after acute myocardial infarction (AMI) with impaired left ventricular function, signs and symptoms of heart failure, or diabetes in the EPHESUS trial according to their reperfusion status. Cox regression models were used to assess the impact of reperfusion status on the association of DBP and systolic blood pressure (SBP) with outcomes in an adjusted fashion. In patients without reperfusion, lower DBP <70 mmHg was associated with increased risk for all-cause death [adjusted hazard ratios (HRs) 1.80, 95% confidence interval (CI) 1.41–2.30; P  < 0.001], cardiovascular death (HR 1.70, 95% CI 1.3–3.22; P  < 0.001), cardiovascular death or cardiovascular hospitalization (HR 1.54, 95% CI 1.26–1.87; P  < 0.001). In patients with reperfusion, the risk increase at low DBP was not observed. At low SBP, risk increased independently of reperfusion. A sensitivity analysis in the subgroup of patients with optimal SBP of 120–130 mmHg showed again risk reduction of reperfusion at low DBP. Adding the treatment allocation to eplerenone or placebo into the models had no effects on the results. Conclusion: Patients after AMIs with a low DBP had an increased risk, which was sensitive to reperfusion therapy. Low blood pressure after MI identifies in patients with particular higher risk. These data support the hypothesis that low DBP in patients with stenotic coronary lesions is associated with risk, potentially involving coronary perfusion pressure and the recommendations provided by guidelines suggesting lower DBP boundaries for these high-risk patients.